Social norms and the impact of early life events on gender inequality - Wei Luo; Wei Huang; Albert Park (Asian Development Bank (ADB), 2024)
We study the influence of social norms in determining the impact of early life exposure to the Great Chinese Famine of 1959-1961 on gender inequality. We model how social norms interact with adverse shocks to affect male and female survival chances and influence subsequent human capital investments. We test these predictions empirically by using the Fifth National Population Census of the People's Republic of China in 2000 that has information on birthplace and estimate a difference-in-differences model that combines cohort and regional variation in exposure to the famine with regional variation in the culture of son preference. We find that son preference buffers the negative impact of intrauterine famine shocks on cohort male-to-female sex ratios and reduces famine's impact on gender inequality in health and education.
Keywords: J13; J16; I24; I26; 330; famine; son preference; sex ratios; human capital investment